Effects of Data Collection Methods on Estimated Household Consumption and Survey Costs : Evidence from an Experiment in the Marshall Islands - Sharp, Michael K.; Buffière, Bertrand; Himelein, Kristen; Troubat, Nathalie; Gibson, John (World Bank, Washington, DC, 2022)
In the Pacific, multitopic household surveys have historically gathered expenditure data using open form diaries completed on paper. This methodology is costly to governments, is burdensome for respondents, and takes substantial time to process the results. Noncompliance and partial compliance in diary keeping can artificially inflate poverty measures, biasing economic statistics. This paper reports findings from an experiment in the Marshall Islands comparing the cost and accuracy of several collection methodologies. Variable costs for the status quo diary survey design are between 2.8 and 4.4 times more expensive than a single-visit seven-day recall survey, with the tablet-based diary being even more costly. The highly monitored diaries give similar results to recall but at much greater cost; the status quo yields data of worse quality as effective completion rates with low monitored diaries are only two-thirds the completion rates of recall-based options. Finally, the paper discusses the implementation challenges associated with the different methods in a capacity-constrained environment.